2014
DOI: 10.1016/j.dental.2013.08.202
|View full text |Cite
|
Sign up to set email alerts
|

Present and future of glass-ionomers and calcium-silicate cements as bioactive materials in dentistry: Biophotonics-based interfacial analyses in health and disease

Abstract: ObjectiveSince their introduction, calcium silicate cements have primarily found use as endodontic sealers, due to long setting times. While similar in chemistry, recent variations such as constituent proportions, purities and manufacturing processes mandate a critical understanding of service behavior differences of the new coronal restorative material variants. Of particular relevance to minimally invasive philosophies is the potential for ion supply, from initial hydration to mature set in dental cements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 67 publications
2
98
0
7
Order By: Relevance
“…1h) and calcium crystal formations (Fig. 2c) probably correspond with calcium hydroxide and/or calcium carbonate compounds (HAp precursors) (Watson et al, 2014). Crystal formations were not detected in XRD analysis because of their small size and proportion with respect to the amorphous phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1h) and calcium crystal formations (Fig. 2c) probably correspond with calcium hydroxide and/or calcium carbonate compounds (HAp precursors) (Watson et al, 2014). Crystal formations were not detected in XRD analysis because of their small size and proportion with respect to the amorphous phase.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of silicon may be important, since silicon is known to facilitate CaP deposition on particles (Leonor et al, 2009), and played a critical role in the binding of CaP to the collagen network (Besinis et al, 2014). Silica NPs have been shown to mediate the formation of CaP precursors, necessary for the subsequent steps of mineralization, acting as a nucleating mineral (Watson et al, 2014). Besinis et al (2014) applied silica and HAp nanoparticles to demineralized dentin and hypothesized that phosphorus binds to silica NPs, thus enhancing remineralization when combined with ionic calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Zn-containing amalgams enhanced the physical, mechanical and electrochemical properties of the restoration, and it also increases the heterogeneity and so, the fatigue resistance of the amalgam microstructure 19 . Zn-rich products at the toothamalgam interface, as ZnSn(OH) 6 , ZnO2, and Zn ++ free 20 , improved the sealing of the dentin-amalgam interface, enhancing the clinical lifetime of this restoration 21 . Previous outcomes have demonstrated that Zn-containing amalgams promoted an increase of nanomechanical properties, and a general augmentation of mineral gradients, ratios and crystallinity in partially mineral-depleted dentin surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Caries-affected dentin (CAD) is partially demineralized and more porous than noncarious dentin with a predominantly intact collagen matrix, whose collagen fibrils retain their banded structure and intermolecular crosslinks 4 . It should be preserved during clinical treatment because it is remineralizable and serves as a suitable substrate for tooth repair 5 and physiologic remineralization 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Caries-affected dentin is partially demineralized and more porous than non-carious dentin with a predominantly intact collagen matrix, whose collagen fibrils retain their banded structure and intermolecular crosslinks [6] . It should be preserved during clinical treatment because it is remineralizable and serves as a suitable substrate for tooth repair [7] and physiologic or therapeutic remineralization [8] . By the time being, amalgam continues to play a major role in restorative dentistry, today [9] , though it is not an ideal material, as the cosmetic appearance is poor and cannot bond to tooth [10] .…”
Section: Introductionmentioning
confidence: 99%